Utilization of Sludge from Textile Wastewater Treatment Plants as Raw Material for Iron Coagulant - Galu Murdikaningrum; Kenny Kencanawati; Bagus R Ramdhani; Rizal Ramdani (Universitas Insan Cendekia Mandiri, 2022)
Treatment of liquid waste using iron coagulant produces a by-product in the form of sludge which requires large handling costs. To reduce environmental pollution and sludge treatment costs, the sludge will be used as raw material for the manufacture of iron coagulant. This study aims to determine whether the sludge from textile WWTP can be used as raw material for iron coagulant. To determine the effectiveness of coagulants made from sludge, this study will compare the results of the coagulation-flocculation process using commercial iron coagulants and iron coagulants made from sludge as well as mixed coagulants with ratios of commercial iron coagulants to iron coagulants made from sludge of 70%, 60%, 50%, 40%, and 30%. The water quality resulting from the coagulation-flocculation process was indicated by pH, color turbidity, Total Dissolved Solid (TDS) and Total Suspended Solid (TSS). The results showed that the water quality of the coagulation-flocculation process was worse when mixed coagulant was used with a smaller ratio of commercial iron coagulant to iron coagulant made from sludge. A mixture of commercial iron coagulant and iron coagulant made from sludge that meets the quality standard for the TSS parameter is a mixed coagulant with a v/v ratio of 70%, while those less than 70% do not meet the quality standard.